2005
DOI: 10.1039/b416811a
|View full text |Cite
|
Sign up to set email alerts
|

Contrasting action of flavonoids on phototoxic effects induced in human skin fibroblasts by UVA alone or UVA plus cyamemazine, a phototoxic neuroleptic

Abstract: The potential protective effects of the flavanol catechin, the flavonol quercetin, the flavones, luteolin and rutin, and the isoflavones, genistein and daidzein, against the photo-oxidative stress induced by ultraviolet A radiation (UVA) and by phototoxic reactions resulting from the interaction of UVA with drugs and chemicals, has been assessed with cultured human skin fibroblasts. Lipid peroxidation and cell death have been chosen as model photobiological damage induced by UVA alone or photosensitized by cya… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
19
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 54 publications
(58 reference statements)
4
19
1
Order By: Relevance
“…Molecules with the ability to scavenge free radicals, therefore, can prevent radiation damage. Evidences demonstrated that genistein has stronger antioxidant actions combining with its capacity to activate the antioxidant systems that results in reduction of the level of freeradical lipid peroxidation products and stabilization of cellular membrane structure, 27,28) Wei et al . reported that genistein provided protection against non-ionizing ultraviolet-B radiation through either direct quenching of reactive oxygen species or indirect anti-inflammatory effects when it was applied to the skin of hairless mice 1h before exposure.…”
Section: Discussionmentioning
confidence: 98%
“…Molecules with the ability to scavenge free radicals, therefore, can prevent radiation damage. Evidences demonstrated that genistein has stronger antioxidant actions combining with its capacity to activate the antioxidant systems that results in reduction of the level of freeradical lipid peroxidation products and stabilization of cellular membrane structure, 27,28) Wei et al . reported that genistein provided protection against non-ionizing ultraviolet-B radiation through either direct quenching of reactive oxygen species or indirect anti-inflammatory effects when it was applied to the skin of hairless mice 1h before exposure.…”
Section: Discussionmentioning
confidence: 98%
“…Genistein (GEN), one of the main soy isoflavone components, occurs naturally in various plant-derived foods and displays very low levels of toxicity in most animal species [11]. In recent years, soybean isoflavones and GEN have consistently drawn widespread attention for their bioactivity in alleviating radiation damage [12,13]. Some studies have demonstrated that GEN can increase the survival rate of radiation-induced myelosuppressed mice [14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…N: normal mice (un-irradiated mice); Rad 6 Gy: Positive control (irradiated mice with dose of 600 rad); EPO: Irradiated mice followed by intraperitoneal injection of HEMAPO Epoetin alfa treatment; D1: Irradiated mice followed by oral administration of low dose of EMSA Eritin (1.04 mg/g BW), D2: Irradiated mice followed by oral administration of normal dose of EMSA Eritin (3.125 mg/g BW); D3: Irradiated mice followed by oral administration of high dose of EMSA Eritin (9.375 mg/g BW). Genistein in soy is a powerful antioxidant and is able to activate the antioxidant system in order to reduce levels of free radicals from lipid peroxidation products, and stabilize the structure of the cell membrane [21,22]. Wei et al (2002) mentions that genistein provides protection against non-ionizing radiation of ultraviolet-B and against reactive oxygen species (ROS), indirectly acting as an anti-inflammatory when genistein was applied to the skin of mice 1 hour before exposure to radiation.…”
Section: Discussionmentioning
confidence: 99%